2021
DOI: 10.1200/cci.20.00117
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of Fitness Tracker Usage to Assess Activity Level and Toxicities in Patients With Colorectal Cancer

Abstract: PURPOSE Performance status (PS) is a subjective assessment of patients' overall health. Quantification of physical activity using a wearable tracker (Fitbit Charge [FC]) may provide an objective measure of patient's overall PS and treatment tolerance. MATERIALS AND METHODS Patients with colorectal cancer were prospectively enrolled into two cohorts (medical and surgical) and asked to wear FC for 4 days at baseline (start of new chemotherapy [± 4 weeks] or prior to curative resection) and follow-up (4 weeks [± … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 38 publications
1
9
0
Order By: Relevance
“…Multiple studies showed that greater postoperative physical activity was correlated with shorter length of stay 28 , 58 , 73–75 , and a reduced risk of readmission following discharge 15 , 73 , 76 , 77 . Higher postoperative step counts were associated with a lower risk of complications 30 , 72–74 , 78–81 , faster gastrointestinal recovery 73 , and lower long-term skeletal muscle loss 82 . Patients with postoperative delirium had similar mobilization in the early postoperative interval and had lower physical activity at 1 month after surgery 83 .…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…Multiple studies showed that greater postoperative physical activity was correlated with shorter length of stay 28 , 58 , 73–75 , and a reduced risk of readmission following discharge 15 , 73 , 76 , 77 . Higher postoperative step counts were associated with a lower risk of complications 30 , 72–74 , 78–81 , faster gastrointestinal recovery 73 , and lower long-term skeletal muscle loss 82 . Patients with postoperative delirium had similar mobilization in the early postoperative interval and had lower physical activity at 1 month after surgery 83 .…”
Section: Resultsmentioning
confidence: 96%
“…Many papers investigated changes in physical activity perioperatively, showing reduced step counts after surgery, with a long return to baseline that may take weeks to months 21 , 25–27 , 29–31 , 58–68 . The recovery trajectory in physical activity differed depending on type of operation 64 , use of laparoscopy 69–71 , need for ICU admission 64 , as well as overall performance status 72 . Romain et al .…”
Section: Resultsmentioning
confidence: 99%
“…In a heterogeneous prospective study of patients with colorectal cancer either undergoing colectomy or starting chemotherapy, there was no significant association between change in step counts in the pretreatment or post-treatment periods and the development of protocol-specified toxicity. 11…”
Section: Discussionmentioning
confidence: 99%
“…Ambulatory activity trackers enable researchers to monitor the type, quantity, and quality of patients’ everyday activities ( 47 , 48 ), and some also assess sleep quality and quantity. Activity trackers may capture many of the preclinical signs of treatment toxicities with limited patient burden ( 49 ). Machine learning–derived algorithms applied to this data could contribute to earlier detection and management of toxicity.…”
Section: Study Measuresmentioning
confidence: 99%